2003
DOI: 10.1083/jcb.200304065
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ligand binding sites in integrin α3β1 regulate matrix adhesion and cell–cell contact

Abstract: The integrin α3β1 mediates cellular adhesion to the matrix ligand laminin-5. A second integrin ligand, the urokinase receptor (uPAR), associates with α3β1 via a surface loop within the α3 β-propeller (residues 242–246) but outside the laminin binding region, suggesting that uPAR–integrin interactions could signal differently from matrix engagement. To explore this, α3−/− epithelial cells were reconstituted with wild-type (wt) α3 or α3 with Ala mutations within the uPAR-interacting loop (H245A or R244A). Wt or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 32 publications
(41 reference statements)
7
92
1
1
Order By: Relevance
“…Cells were fixed and stained with various antibodies and IgG isotype controls as described previously (15). Where indicated, composite images comprising multiple ϫ20 images were tiled using 10% image overlap by Axiovision 4.7 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were fixed and stained with various antibodies and IgG isotype controls as described previously (15). Where indicated, composite images comprising multiple ϫ20 images were tiled using 10% image overlap by Axiovision 4.7 software.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting, Immunoprecipitation, and Immunofluorescence-Tissue and cells were lysed in radioimmuneprecipitation assay buffer supplemented with proteinase and phosphatase inhibitors and immunoprecipitated as described previously (15). Cells were fixed and stained with various antibodies and IgG isotype controls as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…They could perturb the downstream cell adhesion and migration pathways and modulate the cytoskeleton, thus regulating cell motility and migration (40,41). Numerous studies have reported differentially expressed integrins in many cancers.…”
Section: Significancementioning
confidence: 99%
“…Integrins interact with and influence the activity of other membrane-bound cell adhesion molecules including E-cadherin (69). Similar to ␣ 3 -integrin, E-cadherin is expressed in airway epithelial cells but not at airway branching tips, consistent with E-cadherin's roles in adherens junctions to stabilize cell-cell contacts and in establishing and maintaining apico-basal polarity of epithelial cells.…”
mentioning
confidence: 77%
“…The importance of E-cadherin for maintenance of epithelial cell polarity and stability as well as the necessity of integrin-E-cadherin clustering to control cell signaling and epithelial cell stabilization suggests that increased E-cadherin along with increased and aberrant expression of ␣ 2 -integrin may have altered the formation of integrin-E-cadherin heterodimers, thereby contributing to dysregulated cell-adhesion and cellular migration in BPS and CCAM while controlling or preventing any invasive potential of the abnormal airways in these lung lesions (24,47,69). E-cadherin expression is also linked to ␤-catenin signaling with ␤-catenin being bound to its cytoplasmic domain.…”
Section: Discussionmentioning
confidence: 99%